English Swear Words by Indonesian Learners - Latif Amrullah (Journal of English Language Teaching and Linguistics, 2016)
Language functions to convey expression and content, either for their self or for others. Some people tend to use swear words in certain conditions and situation to show their feeling or just to express an inconvenience. In other words, swear word is closely related to anger expression. This paper examines the use of English swear words in certain simulated anger situations in order to know what kinds of swear words that the respondents use. The data were gathered through some simulated anger situations which were made by considering certain social dimensions. The respondents are the university students who were taken randomly through different classes. This study shows that certain English swear words are commonly used by the respondents and the social status of respondents governs as an important aspect.